The escape room [large type] - Goldin, Megan (Wheeler Publishing large print hardcover, 2019)
"Welcome to the escape room. Your goal is simple. Get out alive. In the lucrative world of finance, Vincent, Jules, Sylvie, and Sam are at the top of their game. They've mastered the art of the deal and celebrate their success in style--but a life of extreme luxury always comes at a cost. Invited to participate in an escape room as a team-building exercise, the ferociously competitive co-workers crowd into the elevator of a high rise building, eager to prove themselves. But when the lights go off and the doors stay shut, it quickly becomes clear that this is no ordinary competition: they're caught in a dangerous game of survival. Trapped in the dark, the colleagues must put aside their bitter rivalries and work together to solve cryptic clues to break free. But as the game begins to reveal the team's darkest secrets, they realize there's a price to be paid for the terrible deeds they committed in their ruthless climb up the corporate ladder. As tempers fray, and the clues turn deadly, they must solve one final chilling puzzle: which one of them will kill in order to survive?"--